Early detection of Bronchopulmonary Dysplasia (BPD) in preterm infants using doppler ultrasound technology - Pin Wang; Lihong Duan; Congxin Sun; Yu Chen; Yanyan Peng; Guihong Chen; Lixia Wu; Yan Li (SLAS Technology)
Objective: The purpose of this research is to determine if Doppler ultrasonography technology may be used to forecast the onset of bronchopulmonary dysplasia (BPD) in premature babies in the early postnatal stage. Methods: On days 3, 7, 14, and 28 after delivery, Doppler ultrasonography exams were performed on a prospective cohort of 170 preterm newborns. Measurements were made of parameters such right ventricular output (RVO), systolic-to-diastolic ratio (S/D ratio), pulmonary artery acceleration time (PAAT), and velocity time integral (VTI). The predictive value of these indicators was evaluated using Kaplan-Meier survival analysis and multivariate logistic regression. Results: The severity of BPD was substantially correlated with all assessed Doppler ultrasound parameters (P < 0.05). With an area under the curve (AUC) of 0.76, PAAT in particular demonstrated a reasonable capacity for prediction. A considerably greater cumulative incidence was found by Kaplan-Meier survival analysis. Conclusion: In conclusion, Doppler ultrasonography technology is a useful technique for identifying BPD in premature babies early on. High-risk babies can be efficiently identified by PAAT and VTI in particular, allowing for prompt intervention and possibly better results.